Peer and Community Influences on Adolescent Substance Use in the Context of Adverse Childhood Experiences. (April 2022) - Stritzel, Haley
Both adverse childhood experiences (ACEs) and peer influences consistently predict early tobacco, alcohol, and illicit drug use. However, less research considers how peer and community influences contribute to or modify the association between ACEs and early substance use. This study addresses these gaps in the literature by analyzing multilevel, longitudinal data from the Project on Human Development in Chicago Neighborhoods (PHDCN; N = 1, 912). Unstructured socializing and peer substance use largely explained the association between ACEs and drinking, smoking cigarettes, and illicit drug use in the past month. A history of ACEs magnified the association between peer substance use and the number of cigarettes smoked. Collective efficacy also shaped the associations between peer influences, ACEs, and substance use, but in different ways depending on the substance use outcome analyzed.